Nucleocapsid and matrix proteins of nipah virus produced in Pichia pastoris and their interaction - Narcisse Mary, Sither Joseph Vesudian (2016)
Nipah Virus (NiV) is a zoonotical pathogen belonging to the family of Paramyxoviridae and genus Henipavirus. Its natural reservoir is believed to be fruit bats, Pteropus sp. The outbreaks of NiV in Malaysia, India and Bangladesh recorded high fatality rate imposing a major health risk worldwide. It is classified under Biosafety level 4 pathogen and the production of immunological reagents for assays using the inactivated virus requires BSL 4 facilities which are costly and limited.Recombinant proteins produced in Escherichia coli served as an alternative, however being a prokaryotic expression system, disadvantages such as lack of posttranslational modifications are unavoidable. The nucleocapsid (N) and matrix (M) proteins produced in E. coli expression system were different from the native viral proteins. Thus, the aim of this study was to produce the N and M proteins of NiV in a yeast system, Pichia pastoris, and to study their interaction. The interaction of N and M proteins will help to reveal the role of these proteins in the production of VLPs.The N protein was successfully expressed in P. pastoris and purified using sucrose density ultracentrifugation but was found to be truncated at the C-terminal end.However the recombinant nucleocapsid protein assembled into tightly packed long helical structures as long as 1.5 μm. The M protein of NiV was expressed in P.pastoris and purified using an Immobilized Metal Affinity Chromatography (IMAC) column. The M protein also assembled into large virus-like particles resembling the native virus. However, due to the poor yield and purity of the M protein produced in P. pastoris, an in-silico method called docking was chosen to study the interaction of M and N proteins. The 3-dimensional structures of the N and M proteins of NiV are not available in the Protein Data Bank (PDB) for docking analysis and there are no similar structures available. Therefore, the structures of the two proteins were predicted based on an ab initio method using the I-TASSER web server. The predicted 3D structures generated using ITASSER had a confidence score (C-score) of -0.82 and 0.56 for N and M proteins, respectively. The final models also had a low root-mean-square deviation (RMSD) (9 Å for N and 5.3 Å for M protein) which shows the reliability of the predicted structure. The interaction of N and M proteins was analysed using a molecular docking employing the PatchDock method and refined with the FireDock algorithm. The two proteins were found to interact well with a binding energy of −13.09 kcal/mol. However to validate the docking results,five peptides corresponding to the interacting residues in the M protein were synthesized to study the interaction using an in-vitro assay. The instability of the N protein lead to a simple and less complicated method of interaction study, using fluorescence spectroscopy analysis.. The fluorescence quenching assay demonstrated that peptides M2 and M4 show significant interactions with the NiV N protein with dissociation constant (Kd) values of 12 μM and 17 μM, respectively. This indicates that the M protein interacts with the N protein and proves the M and N proteins interact during the VLP formation.